PENGARUH EDUKASI BERBASIS APLIKASI ANDROID "SI CERDAS POSTPARTUM" TERHADAP PENGETAHUAN IBU POSTPARTUM PRIMIPARA TERKAIT PERAWATAN PAYUDARA PASCA MELAHIRKAN - Nurul Fatihah Auliani, NFA (2021)
The incidence of mastitis still often occurs in Indonesia in post partum mothers who breastfeed their children. One of the causes is the lack of breast care with a history of mastitis. The purpose of this study was to determine the effect of education based on the Android application "Si Cerdas Post Partum" on the knowledge of primiparous post partum mothers regarding postpartum breast care. This study used a quasi-experimental pre and post test one group (intervension) on 40 samples of primiparous postpartum mothers through a total sampling technique mixed with simple random sampling. The results of the statistical test showed that there was a significant effect of the influence on the intervention group using the Si Cerdas Post Partum application on knowledge of postpartum breast care (p value = 0.000). There is a difference in the effect after the intervention between the intervention group on knowledge of breast care. The Smart Post Partum application can be used as a source of information about postpartum breast care. Keyword: breast care, primiparaous mother, application.